2013
DOI: 10.1097/rli.0b013e3182718672
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Dark-Blood T2-Weighted CMR for Evaluation of Acute Myocardial Injury

Abstract: Although FSE-SPAIR demonstrated significantly improved image quality and decreased artifacts, isolated interpretations of each T2-weighted technique demonstrated high specificity but overall low sensitivity for the detection of myocardial injury, with no difference in accuracy between the techniques. However, real-world interpretation in combination with cine and LGE CMR methods significantly improves the overall sensitivity and diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…However T2w-TSE imaging has inherent disadvantages that can compromise image quality and oedema detection. Upto 30% of datasets are non-analysable in studies[ 24 , 143 , 144 ]. New T2w sequences have been studied, with encouraging results (Figure 7 ).…”
Section: Ischaemic Aar and Myocardial Salvage In Amimentioning
confidence: 99%
See 2 more Smart Citations
“…However T2w-TSE imaging has inherent disadvantages that can compromise image quality and oedema detection. Upto 30% of datasets are non-analysable in studies[ 24 , 143 , 144 ]. New T2w sequences have been studied, with encouraging results (Figure 7 ).…”
Section: Ischaemic Aar and Myocardial Salvage In Amimentioning
confidence: 99%
“…It could be argued that since MSI adjusts IS for the extent of AAR, it may have less inherent variability than IS. Since up to 30% of AAR datasets have been deemed non-diagnostic in previous studies[ 24 , 143 , 144 ], this may impact on the robustness of MSI quantification whereas IS datasets are exceptionally rarely excluded based on image quality. It is not clear currently whether IS or MSI is the better measure of revascularisation success post PPCI.…”
Section: Ischaemic Aar and Myocardial Salvage In Amimentioning
confidence: 99%
See 1 more Smart Citation
“…T2-weighted (T2w) CMR sequences are helpful to detect increased in vivo myocardial water content and offer a noninvasive tool to differentiate between acute and chronic disease [5]. T2w dark-blood sequences are currently used and widely accepted [6]. However, this sequence type can suffer from signal loss in higher heart rates and poor contrast between myocardium and blood in areas of insufficient blood signal suppression [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…If cut-off values > 1.9 were used for the T2 ratio in the studies, sensitivity values of 45 -100 % and specificity values of 50 -100 % were obtained ( • " Table 11), the variations probably being attributable to the different scanner types and sequences [3,16]. Srichai et al [30] therefore demonstrated a high specificity but overall a low sensitivity for the diagnostic performance of T2-weighted CMR in the evaluation of acute myocardial injury (FSE-SPAIR: sensitivity 29 %, specificity 93 %, PPV 67 %, NPV 73 %; FSE-SPIR: sensitivity 38 %, specificity 91 %, PPV 67 %, NPV 75 %, with no difference in accuracy between the techniques). Surely the role of isolated T2-weighted imaging has to be recognized as limited in the diagnosis of myocarditis.…”
Section: Tissue Characterizationmentioning
confidence: 99%